Effect of red light on the composition of metabolites in tea leaves during the withering process using untargeted metabolomics. (4th September 2021) - Lin, Jiazheng; Liu, Fei; Zhou, Xiaofen; Tu, Zheng; Chen, Lin; Wang, Yuwan; Yang, Yunfei; Wu, Xun; Lv, Haowei; Zhu, Hongkai; Ye, Yang
Abstract: BACKGROUND: Red light withering significantly improves the sensory flavor qualities of tea, although changes in metabolites during this process have not been systematically studied until now. The present study comprehensively analyzes metabolites in withered tea leaves at 2‐h intervals up to 12 h under red light (630 nm) and dark conditions using ultra performance liquid chromatography‐high resolution mass spectrometry (untargeted metabolomics). RESULTS: Ninety‐four non‐volatile compounds are identified and relatively quantified, including amino acids, catechins, dimeric catechins, flavonol glycosides, glycosidically‐bound volatiles, phenolic acids and nucleosides. The results show that amino acids, catechins and dimeric catechins are most affected by red light treatment. Ten free amino acids, theaflavins and theasinensin A increase after red light irradiation, whereas epigallocatechin gallate and catechin fall. CONCLUSION: The present study provides a comprehensive and systematic profile of the dynamic effects of red light on withering tea and a rationale for its use in tea processing quality control. © 2021 Society of Chemical Industry.